A cross sectional study of how people diagnosed with a bacterial sexually transmitted infection inform their partners. (18th September 2014) - Knight, Vickie; Ryder, Nathan; Bourne, Chris; McNulty, Anna
Abstract : Objectives: To investigate the methods used by patients diagnosed with a sexually transmissible infection (STI) to inform their partners during contact tracing. Methods: At a large Australian sexual health clinic between March and May 2010, we undertook a retrospective, cross sectional analysis of the methods used by patients diagnosed with a bacterial STI to inform their partners. Results: Of the 172 index patients contacted 1 week after treatment, 163 (95%) chose patient referral, 3 (2%) provider referral and 6 (3%) could not contact any partners. Index patients nominated 1010 sexual partners of whom 494 (49%) were reported as contactable. A total of 447/494 (91%) of these partners were successfully informed; telephone (37%) and face to face (22%) were the most used methods. After multivariate analysis, predictors of using face to face contact methods were age <30 years (AOR: 2.8; 95% CI 1.4 to 5.7), fewer than 2 sexual partners (AOR 3.6; 95% CI 1.7 to 7.6) and speaking a language other than English (adjusted OR (AOR) 3.1; 95% CI 1.3 to 7.2). The single predictor of using interactive contact methods (face to face+telephone) was reporting fewer than 2 sexual partners (AOR 2.7; 95% CI 1.3 to 5.5). People diagnosed with syphilis were significantly less likely to use an interactive contact tracing method (AOR 0.24; 95% CI 0.09 to 0.67). Conclusions: Most patients diagnosed with a bacterial STI at our sexual health clinic report informing their contactable partners directly either face to face or by telephone. Electronic communications methods were more popular for people with more sexual partners and those with syphilis. Effective contact tracing requires access to a range of methods for patients to inform their partners.